My style, my food, my waste! Consumer food waste-related lifestyle segments. (March 2021) - Aschemann-Witzel, Jessica; de Hooge, Ilona E.; Almli, Valérie L.
Abstract: Adapting responsible food marketing practices to different customer types can make a valuable contribution to reducing food waste. The current study investigated the relation between food (waste)-related lifestyle patterns and self-reported food waste, choices for suboptimal food, and food waste awareness using a survey with 4214 consumers across five Northern and Western European countries. Results show differences in food wastage, suboptimal choices, and awareness for five clusters of consumers identified on the basis of food (waste)-related lifestyle patterns. Findings of commonalities allow deriving food marketing actions targeted to these different consumer lifestyles. Highlights: Food waste in consumer households is a sustainable development challenge. We relate food(waste)-related lifestyle to waste, awareness, and socio-demographics. Five segments emerge across five Northern/Western European countries. Distinct marketing approaches are needed depending on the segment in question. Food retailers and NGOs working with reducing food waste can apply segmentation.